The effect of servant leadership on employees' extra‐role behaviors in NPOs: The role of work engagement - Aboramadan, Mohammed; Hamid, Zeeshan; Kundi, Yasir Mansoor; El Hamalawi, Eissa (Nonprofit management & leadership, 2022)
Building on the social exchange theory and the rule of reciprocity, this study examines the effect of servant leadership on employees' extra‐role behaviors (innovative work behavior, organizational citizenship behavior, and creativity) in the nonprofit organizations (NPOs) context. In this model, we examined work engagement as a mediator. Data were collected in two waves from 309 employees and complemented by their supervisors' evaluations. We analyzed the data using structural equation modeling and the Baron and Kenny method for mediation. The findings reveal that servant leadership exerts a positive influence on employees' extra‐role behaviors. Furthermore, work engagement plays a significant role as a mediator in the relationship between servant leadership and extra‐role behaviors. Finally, discussion, implications, and limitations are presented.